Manajemen Program Pendidikan Anak Usia dini di TK Al-Irshan Kota Makassar - Febriansa, Febriansa; Gaffar, Syamsul Bakhri (JAPPA: Jurnal Andragogi Pedagogi dan Pemberdayaan Masyarakat, 2024)
This research aims to describe the management of early childhood education programs at Al-Irshan Islamic Kindergarten Makassar. This research uses a qualitative research approach. The subjects of this research were the principal and teachers at the Al-Irshan Islamic Kindergarten. Data were analyzed using descriptive analysis through interviews with the principal and teachers who teach at the Al-Irshan Islamic Kindergarten. The research results show that the management of the early childhood education program at the Al-Irshan Islamic Kindergarten consists of planning, organizing, implementing, and supervising. The research results illustrate (1) that the planning shows that the management has compiled and developed the school's vision and mission as well as determined the program that will be implemented. (2) Organization describes the duties and responsibilities of school principals and teachers as structured. (3) Implementation illustrates that the principal and teachers have carried out their teaching responsibilities well. (4) Supervision describes that the school principal supervises teacher performance so that they carry out their duties and responsibilities well.